A high-contrast coronagraph for direct imaging of Earth-like exoplanets: design and test**Supported by the National Natural Science Foundation of China. (March 2015) - Liu, Cheng-Chao; Ren, De-Qing; Dou, Jian-Pei; Zhu, Yong-Tian; Zhang, Xi; Zhao, Gang; Wu, Zhen; Chen, Rui
Abstract: A high-contrast coronagraph for direct imaging of an Earth-like exoplanet at the visible band needs a contrast of 10 −10 at a small angular separation of 4λ/ D or less. Here we report our recent laboratory experiment that approaches these limits. Our test of a high-contrast imaging coronagraph is based on our step-transmission apodized filter. To achieve this goal, we use a liquid crystal array as a phase corrector to create a dark hole based on our dedicated algorithm. We have suppressed the diffraction and speckle noise near the point image of a star to a level of 1.68 × 10 −9 at 4λ/ D, which can be used for direct imaging of Jupiter-like exoplanets. This demonstrates that a telescope incorporating a high-contrast coronagraph in space has the potential to detect and characterize Earth-like planets.